LUNAR: A Practical Anonymous Network Simulation Platform. (4th May 2022) - Zheng, Xianchun; Yan, Haonan; Wang, Rui; Zhang, Ziwei; Li, Hui
Abstract : With the expansion of cyberspace and the increasing importance of users for privacy protection, anonymous network research has been further developed, especially for the numerous internet of things (IoT) devices. However, when we repeat the existing experiment in an anonymous network, there are many problems such as too old version, low realism, poor operability, and so on. In this paper, we analyzed the design requirements and topology of the new experimental platform. Two topologies with different levels of complexity are designed. We also set up a practical anonymous network simulation platform called LUNAR with virtualization, software-defined networking (SDN), and other technologies to solve those problems. The platform we proposed supports multiprotocol and reproducible complex networks with centralized management. Finally, we implement our simulation platform and reproduce two typical attacks, that is, time-linked Tor node reset attack and website fingerprint attacks on The Onion Router (Tor) network, to evaluate the platform. Experiments results indicate the practicality and superiority of our simulation platform in terms of anonymous network simulation.